Fine needle aspiration cytology, with immediate reporting, in the outpatient diagnosis of breast disease. - Dehn, T. C. (Royal College of Surgeons of England, 1987)
One hundred and fifty one new patients attending a breast clinic over a 6 month period underwent fine needle aspiration cytology (FNAC), with immediate reporting of the smears in the clinic. Thirty nine smears (25.8%) were classified as unequivocally malignant, 10 (6.6%) as being suspicious of malignancy, 61 (40.3%) as benign and 41 (27.1%) were acellular. There were no false positive diagnoses and only one false negative cytological diagnosis of breast cancer [corrected]. Immediate reporting of results enabled the diagnosis to be discussed with the patient at the first attendance and allowed improved surgical management of both benign as well as malignant breast disease.